GUIDANCE AND COUNSELING METHOD AS PSYCHOLOGICAL APPROACH FOR TEACHING ENGLISH SPEAKING SKILL - Zulfah Zulfah (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2016)
The teaching objective is to give knowledge and skills for students. There are two factors influence students in learning; they are external factor and internal factor. The internal factor includes motivation, interest, attitude, and intelligence. This method is a speaking teaching method with psychological approach to stimulate and motivate students to speak. It uses students’ speaking problems as teaching materials and the techniques of this method are inspired from guidance and counseling techniques